Organizational Citizenship Behavior (OCB) Improvement Strategy through Strengthening Servant Leadership, Culture of Trusting Behavior, and Job Satisfaction - Aceng Abdul Aziz; Soewarto Hardhienata; Sri Setyaningsih (Return : Study of Management, Economic and Bussines, 2024)
This research aims to examine the strategies for improving Organizational Citizenship Behavior (OCB) among teachers through strengthening servant leadership, work culture, mutual trust behavior, and job satisfaction. Utilizing a quantitative survey method, the study investigates the direct and indirect influences of these variables on OCB among teachers at private Islamic schools in Sukabumi Regency. The results show a significant direct influence of servant leadership, work culture, mutual trust behavior, and job satisfaction on teachers' OCB. Furthermore, the study reveals that mutual trust behavior and job satisfaction play mediating roles between servant leadership, work culture, and OCB. However, mutual trust behavior is not effective as a mediator between work culture and OCB, indicating that work culture can directly influence OCB without the need for mediation. This research contributes to the understanding of OCB improvement strategies and offers practical solutions for policymakers and educational leaders to enhance teacher performance and overall education quality.